Cisco Networking Academy Program: first-year companion guide (Cisco Systems, 2001)
This book supports and reinforces the Web-based curriculum for the Cisco Networking Academy Program, while reinforcing concepts pertaining to CCNA certification. The first-year guide provides an in-depth discussion of the OSI reference model layers and path determination, in addition to the configuration details for IP routing and addressing, subnetting topics, and basic router configuration and operation. The instructional materials for the First-Year Companion Guide follow the instructional style and format that Cisco Systems has created for the Cisco Networking Academy Program and is the only print companion that Cisco Systems reviewed and endorses for the Cisco Networking Academy